2016
DOI: 10.1007/s10800-016-1032-3
|View full text |Cite
|
Sign up to set email alerts
|

Insights into solid electrolyte interphase formation on alternative anode materials in lithium-ion batteries

Abstract: To gain new insights into the formation of the solid electrolyte interphase (SEI), as a basis for the safe and efficient use of new anode materials, we studied SEI formation on silicon and lithium titanate (LTO) anodes by electrochemical impedance spectroscopy (EIS) and ex situ X-ray photoelectron spectroscopy (XPS) measurements. While EIS measurements performed at equidistant voltage intervals provided insights into the SEI formation process, ex situ X-ray photoelectron spectroscopy (XPS) measurements supplie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…These peaks are related to aliphatic and aromatic hydrocarbons in the polymer binder. 62 After 5 cycles, new peaks are also seen in the F1s spectrum at 686 eV and P2p spectrum at 134.5 eV which indicates characteristic of Li x PF y , Li x PF y O z , and LiF. 63 These new peaks demonstrate the changes of the elemental concentrations.…”
Section: Resultsmentioning
confidence: 94%
“…These peaks are related to aliphatic and aromatic hydrocarbons in the polymer binder. 62 After 5 cycles, new peaks are also seen in the F1s spectrum at 686 eV and P2p spectrum at 134.5 eV which indicates characteristic of Li x PF y , Li x PF y O z , and LiF. 63 These new peaks demonstrate the changes of the elemental concentrations.…”
Section: Resultsmentioning
confidence: 94%
“…It is widely reported in the literature that silicon anodes endure substantial volumetric expansion/contraction (280-400%) due to repeated (de-)lithiation, giving rise to high internal stresses within the anode, which lead to continuous repair of the damaged SEI and ultimately result in the consumption of cyclable lithium and capacity fade [3,[5][6][7][8][9][10][11][12][13][14]. In an initial effort to monitor this characteristic behavior, it was observed that applying external pressure perpendicular to the cell's electrodes by constraining it volumetrically improved both its energy and power capabilities, as reported in our previous work [21].…”
Section: The Influence Of Pressurementioning
confidence: 99%
“…Silicon (Si) presents an attractive alternative to the graphite anode material currently used in conventional Li-ion batteries owing to its natural abundance, significantly higher volumetric capacity and specific capacity (2194 Ah/l vs. 719 Ah/l for Li 15 Si 4 and LiC 6 ; 3579 mAh/g vs. 372 mAh/g for Si and graphite) [3,4]. However, Si anodes have shown poor cyclability as a result of substantial volumetric expansion/contraction (280-400%) [3,[5][6][7][8][9][10][11][12][13][14] due to repeated (de-)lithiation, giving rise to high internal stresses within the anode. Plenty of research [5][6][7][8][9][10][11][12][13][15][16][17] is available in the literature, identifying the aging mechanisms induced by electrochemical cycling of Si anode half-cells as: (1) deterioration of the electrode's structural integrity due to pulverization; (2) disconnection between the current collector and electrode due to (de-)lithiation-induced stress; (3) consumption of cyclable lithium in the reformation process of the damaged Solid Electrolyte Interface (SEI).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, until now the great majority of battery experiments is conducted based on single cell preparation. Coin cells and pouch packaged cells are used for two-electrode measurements while three-electrode measurements are carried out with sophisticated mechanical constructions like T-cells (Garcia et al 2016;Loveridge et al 2016) or El-cells (Steinhauer et al 2017).…”
Section: Introductionmentioning
confidence: 99%